1989
DOI: 10.1002/jlb.46.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Tumor Necrosis Factor Expression in the Human Mono-Mac-6 Cell Line by Lipopolysaccharide

Abstract: Mono-Mac-6 cells, but not U937 cells, can be induced to rapidly express tumor necrosis factor (TNF) mRNA and protein when triggered with lipopolysaccharide (LPS) at 1 microgram/ml. Preincubation of the cells for 3 d with low amounts of LPS (10 ng/ml) results in nearly complete suppression of TNF secretion. This downregulation appears to occur at the pretranslational level since specific mRNA is virtually undetectable under these conditions. By contrast, the same preincubation with 10 ng/ml LPS results in enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 8 publications
2
15
0
1
Order By: Relevance
“…Thus, regulatory mechanisms must exist to limit Mbk responses to LPS during infection. The adaptive responses ofMb to LPS that we and others have demonstrated provide a way for regulating cytokine release during endotoxemia (20,(33)(34)(35)(36). In the present studies we have shown that LBP promotes LPSinduced adaptation, as M4 adapted using LPS-LBP com- (37) showed that LPS partial structures could block cell responses to LPS without interfering with CD 14-dependent uptake of LPS.…”
Section: Monocytessupporting
confidence: 59%
“…Thus, regulatory mechanisms must exist to limit Mbk responses to LPS during infection. The adaptive responses ofMb to LPS that we and others have demonstrated provide a way for regulating cytokine release during endotoxemia (20,(33)(34)(35)(36). In the present studies we have shown that LBP promotes LPSinduced adaptation, as M4 adapted using LPS-LBP com- (37) showed that LPS partial structures could block cell responses to LPS without interfering with CD 14-dependent uptake of LPS.…”
Section: Monocytessupporting
confidence: 59%
“…Studies of endotoxin tolerance induced in vitro (26)(27)(28)(29) and in vivo (24,30,31 ) in animals have shown a decrease in the production of several cytokines by macrophages, including dotoxin-induced synthesis of TNFa, IL-I:, and IL-6 of blood monocytes obtained from humans with the sepsis syndrome was recently reported (32). Another recent study found tolerance to endotoxin-induced synthesis of putative IL-1 bioactivity in monocytes from two children with Hemophilus influenza meningitis (33).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested to be controlled at the cellular level (Greisman et al, 1966) (Freudenberg and Galanos, 1988). LPS tolerance was then adapted to in vitro treatment of monocyte/macrophage cell lines like Mono Mac 6 or RAW 264.7 (Haas et al, 1989;Virca et al, 1989) and here it was shown that the TNF gene was down-regulated at the mRNA level. While downregulation of TNF is the salient feature of LPS tolerance other products of monocytes may even be upregulated (Zhang and Marrison, 1993;Knopf et al, 1994;West et al, 1997) and this includes anti-inflammatory molecules like IL-10 and IL-1 receptor antagonist Randow et al, 1995).…”
Section: Discussionmentioning
confidence: 84%
“…When stimulated with LPS repeatedly, monocytes/ macrophages lose their ability to respond (Haas et al, 1989;Virca et al, 1989;reviewed by Ziegler-Heitbrock, 1995), a process termed desensitization or tolerance. In monocytes tolerance appears to be mediated by an upregulation of the p50 (NF-B1) gene product, which in the nucleus blocks transactivation of cytokine genes.…”
Section: Introductionmentioning
confidence: 99%